PENGARUH KOMPOSISI MEDIA TANAM DENGAN KONSENTRASI PUPUK CAIR TERHADAP PERTUMBUHAN TANAMAN ANGGREK DENDROBIUM (Dendrobium sp.) - Febrizawati '; Murniati '; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Orchids are very popular ornamental plant because it has a diverse kind. The flowers are used for various purposes. One way to increase the growth of Dendrobium orchid by using a mixture of planting media and fertilizer through the leaves, because the fertilizer is already contained nutrients needed by plants orchid. The study aimed to obtain the composition of planting medium with a good concentration of liquid fertilizer for the growth of Dendrobium orchid (Dendrobium sp.) and conducted experimentally at Gerai Tanaman Hias Intan Bertuah in Jl. Arifin Ahmad, Pekanbaru, Riau by using Rancangan Acak Kelompok (RAK) consist of 9 treatment (media fern, wood charcoal, coconut husk, broken bricks with Growmore concentrations of 0.5, 1. 5 and 2.5 g/liter of water) with 3 replications. Each experimental unit contained 3 plants and 81 population. The parameters measured were the number of shoots, plant height, stem diameter, leaf length and leaf number. The results showed that treatment with the composition of planting media with concentration of Growmore fertilizer had not significant effect on all parameters was observed that the number of shoots, plant height, stem diameter, leaf length and number of leaves, whereas treatment ferns planting media composition, wood charcoal, coconut fiber with Growmore 1.5 g/liter of water gives the best results for the parameters of the number of shoots, plant height and number of leaves on the growth of Dendrobium orchids (Dendrobium sp.). Keyword : Dendrobium orchids, planting media, fertilizer Growmore